Interpersonal behaviors questionnaire in sport: psychometric analysis with romanian professional athletes. - Alexe, D. I.; Cîrtita, B. C.; Tohanean, D. I.; Larion, A.; Alexe, C. I.; Dragos, P.; Burgueño, R. (Perceptual and Motor Skills, 2023)
Building upon self-determination theory, our objective in this research was to adapt and analyze psychometrically the Interpersonal Behaviors Questionnaire (IBQ) in sport. Our participants were 642 professional athletes (55.14% men, Mage = 22.81) who completed an online survey measuring their perception of coaching behaviors, need satisfaction, need frustration, and motivation. The results showed a good fit for the 24-item IBQ with a six-factor correlated model (X2/df = 4.178; CFI = .925; TLI = .912; SRMR = .048; RMSEA = .070), and we obtained evidence supporting its convergent and discriminant validity. The analyses also underpinned measurement invariance across gender, age, and sport, and confirmed good reliability. Criterion validity was met by positive associations of autonomy-supportive, competence-supportive, and relatedness-supportive behaviors with need satisfaction and autonomous motivation; and of autonomy-thwarting, competence-thwarting and relatedness-thwarting behaviors with need frustration, controlled motivation and amotivation. The adapted IBQ can be applied to the assessment of professional Romanian athletes` perceptions of need-supportive and need-thwarting coaching behaviors.